Etika Politik Islam Pada Pileg 2019 Perspektif Nahdhatul Ulama Lubuklinggau - Saputra, Reksi (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2022)
This thesis discusses Islamic Political Ethics During General Elections in the Perspective of Nahdlatul Ulama (Study of Nahdlatul Ulama Lubuklinggau Ulama and Politicians). This study uses a qualitative type of research method, this study aims to determine the ethics of Islamic politics at the time of the general election in the perspective of scholars and politicians from Nahdlatul Ulama, Lubuklinggau City, South Sumatra Province. There were six informants in this study, consisting of three scholars and three politicians who joined the Nahdlatul Ulama group of Lubuklinggau City. Data and information were obtained and collected from interviews with three ulama and three Nahdlatul Ulama politicians in Lubuklinggau City. This study discusses Islamic political ethics in the perspective of ulama and politicians from the Nahdlatul Ulama City of Lubuklinggau which is then associated with the theory of political ethics according to Nurchlolish Madjid, namely democracy, justice, and pluralism and the theory of political ethics according to Ibnu Miskawaih, namely the theory of the middle way (Nadzar Aus'at). The results of this study indicate that political ethics at the time of the general election in the perspective of Ulama from Nahdlatul Ulama Lubuklinggau City are Islamic political ethics such as honest and fair ethics, polite political ethics, and trustworthy ethics. Then for political ethics during general elections in the perspective of politicians from the Nahdlatul Ulama Lubuklinggau City are Islamic political ethics such as unity, peace and deliberation.